Food scarcity in third world countries: causes and solutions (Journal of the College of Basic Education, 2024)
The issue related to food is among the most significant problems facing Third World countries, as the spread of hunger is not only related to the lack of sufficient food, but it is also connected to the inability of some individuals to obtain food because of the decline in purchasing power and the materials specified for them. The year 2023 saw an unexpected increase in food prices and a shortage in the world's food supply. These worsening crises in different parts of the world were the result of many complex geopolitical, natural as extreme temperatures, floods and droughts caused by climate change. Studies have also indicated that food security is also affected by population factors, as population growth is considered the main factor in increasing food scarcity. This population increase has led to an imbalance in the level of demand and supply, as well as urban expansion at the expense of agricultural land, as well as the role of man in natural resources and the destruction of the environment, which has led to the agricultural sector declined. The Ukrainian invasion also led to higher fuel and fertilizer prices, causing further food shortages, and increasing prices. As well as the economic crisis during the Corona pandemic, food security is also affected by natural factors such as harsh climatic conditions such as high temperatures, lack of rain, increased evaporation, low water levels and its misuse. To achieve food security, comprehensive development plans are necessary to confront the challenges facing it.